The Mnemonic Correction Becomes Meaningful Through Focus Group Discussion in Chemistry Learning - Sri Winarni; Syahrial Syahrial (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2022)
One of the concerns in the learning process is the meaning of writing mnemonics to help students memorize chemistry concepts. The research aimed to correct mnemonics in learning presentation by prospective chemistry teachers' students to be meaningful. The research used constructive design and qualitative methods. The researcher was the main instrument for the microteaching course. Data were collected through observation, focus group discussions (FGD) based on cognitive conflict, and documentation analysis. The results showed that it was found that two prospective chemistry teachers’ students from different groups presented the same mnemonic with less meaningful. The mnemonic was used to memorize the halogens (group 17 of the periodic table). The less meaningful mnemonic generally comes from social media. Based on the group discussion, the students of prospective chemistry teachers obtained 18 mnemonics with meaningful values.Prospective teachers must be able to improve mnemonics in learning to make it more meaningful, one way being to integrate ethnoscience aspects. It was suggested that there should promote creativity in developing learning that encourages positive attitudes to strengthen character education.